Evaluation of Transdermal Formulations: A Technical Note - Mudasir Mohamad, Roheena Jan (Journal of Applied Pharmaceutical Science)
A simple, selective, precise and stability-indicating Isocratic high-performance chromatographic method of analysis for adapalene as a model lipophylic drug in Transdermal (gel) formulations was developed. Mobile phase consisted of acetonitrile(ACN), tetrahydrofuran (THF) and phosphate buffer (PB) (pH-2.5; 0.01 M) in the ratio of 30:40:30 respectively. This mobile phase was found to give adequate results in terms of peak shape, symmetry, tangent and tailing. Retention time (RT) for adapalene was found to be 2.4 with run time of 5 minutes. Samples were subjected to acid, alkali hydrolysis, oxidation, thermal, humidity and photodegradation. The whole analysis was carried out at the wavelength of 272 nm. The linear regression analysis data for the calibration plots showed good linear relationship with r2 = 0.9995 with respect to peak area in the concentration range of 14-26μg/ml.The mean value of correlation coefficient; slope and intercept were 0.9995, 9060.51 and 1282. The method was validated for precision, specificity, recovery and robustness, in accordance with ICH guidelines. The drug undergoes degradation under basic (alkaline) conditions. This indicates that the drug is susceptible to base hydrolysis. Statistical analysis proves that the method is reproducible, selective and accurate for the estimation of said drug. As the method could effectively separate the drug from its degradation product, it can be employed as a stability-indicating one.
Keywords: Adapalene analysis, HPLC method,validation, Stability indicating